A New Risk Assessment Methodology Based on Control Limits - Ali Kokangül; Cansu Dağsuyu; Şeyda Taşkınırmak; Müfide Narlı (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Operating rooms where surgical procedures are conducted involve hazards under various groups and potentially many health problems may arise from these hazards. The degree of the importance of the hazard in each risk group varies according to the groups and it is important to reflect this situation in the risk analyses. In the present study, the dangers may occur in the main groups, namely physical, chemical, and psychological hazard groups in the operating rooms, and the potential health problems that may result from these hazards were evaluated with Failure Mode Effect Analysis (FMEA) method for the first time. By taking the distribution of the FMEA values about the health problems due to hazards that may occur in each main group into consideration, a new approach is suggested in this study. With the new scale that is created based on the average and standard deviation of FMEA values, the comparative importance of the hazards within their groups was revealed. Thus, considering the comparative evaluations, the degrees of importance for health problems in terms of physical, chemical, psychological, and biological categorization were put forth. The COVID-19 outbreak caused a pandemic in the world was also considered in the biological risk class in the study. At the end of the study, the most critical health problems in the operating rooms were detected to be from the risk group resulting from chemical conditions.